THE ROLE OF SCHOOL PRINCIPAL IN OVERCOMING TEACHERS’ OBSTACLES TO DEVELOP THE INDEPENDENT CURRICULUM IN AN ELEMENTARY SCHOOL - Wulandari, Rizki Isma; Nasution, Ammi Thoibah; Rizky, Vega Bintang (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2023)
Changes during the transition period from the 2013 curriculum to the independent curriculum have caused several obstacles for the school community, including the teachers who need to adjust their competencies to the latest curriculum. Therefore, the school principal plays a crucial role in overcoming these obstacles. The purpose of this study is to reveal the role of school principal in overcoming teachers’ obstacles in developing the independent curriculum in elementary schools. This research used a case study method through a qualitative approach with Ngupasan State Elementary School as the location of the study. The subjects of this study were the principal, the teachers, and some students. The data collection techniques consisted of observation, interviews, and documentation. To obtain valid data, a data validity test was carried out through data triangulation by using the technical triangulation and source triangulation. The data analysis technique consisted of data reduction, presentation, and verification. The results of this study show that, to overcome teachers’ obstacles in developing the independent curriculum in elementary schools, the principal acts as a decision maker, mentor, liaison, director, leader, and coordinator with such efforts as a) making bold and firm decisions or decisions by deliberation, b) accepting the opinions/input/suggestions from each teacher, c) providing guidance and direction for teachers who have difficulty in teaching, d) serving as a liaison with the school committee, e) giving solutions, motivation, and support for teacher performance, f) focusing on school programs that are derived from the school's vision and mission, g) helping teachers with independent training to learn the PMM application (Platform Merdeka Mengajar), h) carrying out evaluations once a quarter, and i) coordinating facilities, infrastructure, and the needs of teachers and students. Based on these findings, elementary schools that encounter obstacles in developing the independent curriculum, especially in the teacher aspect, should be able to make the abovementioned efforts to allow optimal implementation of the independent curriculum.